A Survey Study on Social Behaviors towards Nepali Army - Singh Khadka, Bhoj (Unity Journal, 2022)
Humans interact among themselves, and they have different perceptions of public institutions based on their individual approaches and attitudes. Behavior is an interactive product of emotion, thought, and feeling. It is usually resulted from people’s perceptions and activities. Notably, social relation, welfare, accountability, rule of law, democratic culture determines the social behaviors of institutions. An in-depth study of social responses about any work or institution through social media has remained unsearched. This study aims to assess social behaviors towards Nepali Army. To fulfill this objective symbolic behaviors: happy, sad, surprised, excited and outraged on news about the Nepali Army published in Online Khabar were analyzed by deploying a quantitative research method. Out of 138, the 28 news were found as per pre-determined news themes and used for study. The findings of the study reveals that 84.5 % and 86.2 % were happy face behaviors on news on the Nepali Army’s social welfares works and military diplomacy on international controversial issues respectively. Likewise, 91.7 % were sad face behaviors on news on sad events for the Nepali Army. This study strongly indicates that Nepali people are satisfied with the work culture of the Nepali Army and that the Nepali Army has a high reputation in the public sphere. The study result also reveals that Army has been contributing to nation development to keep public sentiments as a central by respecting democratic principles. Good deeds have good comments or happy behaviors. Digital media comments are spontaneous; these comments judge the reputation of the institutions fairly.